2021
DOI: 10.1001/jamaneurol.2021.1101
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Recurrent Stroke Risk in Patients With a Carotid Web

Abstract: IMPORTANCEA carotid web (CW) is a shelf-like lesion along the posterior wall of the internal carotid artery bulb and an underrecognized cause of young stroke. Several studies suggest that patients with symptomatic CW have a high risk of recurrent stroke, but high-quality data are lacking.OBJECTIVE To assess the 2-year risk of recurrent stroke in patients with a symptomatic CW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 28 publications
4
22
1
2
Order By: Relevance
“…However, there was no statistical difference in hematological indexes between the two groups. In this study, the proportion of male CaW patients was higher than that of female CaW patients, which contradicted the previous conclusion that there were more female patients than male patients ( 26 , 27 ). This may be due to selection bias in the preponderance of male patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, there was no statistical difference in hematological indexes between the two groups. In this study, the proportion of male CaW patients was higher than that of female CaW patients, which contradicted the previous conclusion that there were more female patients than male patients ( 26 , 27 ). This may be due to selection bias in the preponderance of male patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Most of these patients were treated with antiplatelet therapy. However, the incidence of recurrent stroke was relatively higher in patients receiving anticoagulant therapy ( 27 ). Therefore, antiplatelet therapy is a reasonable treatment strategy in the patients with transient ischemic stroke or minor stroke ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…A matched case-control study showed 23% ipsilateral CaW in anterior carotid cryptogenic strokes versus none on trauma control cases 10. Patients with symptomatic CaW have been demonstrated to have pronounced rates of recurrent ischemic events, ranging from 17% to 71% and commonly occurring despite the use of antithrombotics 1 3 5 8 11…”
Section: Introductionmentioning
confidence: 99%
“…Baseline data of 3439 adult patients with anterior circulation large-vessel occlusion stroke who underwent endovascular treatment showed that 30 (0.9%) of them were complicated by ipsilateral symptomatic carotid web. 12 Semerano et al found that, in 1430 patients with large-vessel occlusion stroke treated by endovascular thrombectomy, 11 (0.7%) had a symptomatic carotid web. 13 All of them achieved successful angiographic reperfusion (modified Thrombolysis in Cerebral Infarction 2b-3) after endovascular thrombectomy.…”
Section: Discussionmentioning
confidence: 99%